2014
DOI: 10.1155/2014/239791
|View full text |Cite
|
Sign up to set email alerts
|

Bone Healing by Using Ilizarov External Fixation Combined with Flexible Intramedullary Nailing versus Ilizarov External Fixation Alone in the Repair of Tibial Shaft Fractures: Experimental Study

Abstract: Purpose. Our research was aimed at studying the radiographic and histological outcomes of using flexible intramedullary nailing (FIN) combined with Ilizarov external fixation (IEF) versus Ilizarov external fixation alone on a canine model of an open tibial shaft fracture. Materials and Methods. Transverse diaphyseal tibial fractures were modelled in twenty dogs. Fractures in the dogs of group 1 (n = 10) were stabilized with the Ilizarov apparatus while it was combined with FIN in group 2 (n = 10). Results. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…AFM topography images for VDF-TeFE (a), HAP coating (c) and DCPA coating (e) and potential maps for VDF-TeFE (b), HAP coating (d) and DCPA coating (f).It is known that a rough surface structure of CaP coatings stimulates the attachment of osteoblasts and differentiation of multipotent MSC into osteoblasts in in vitro systems and bone formation in in vivo systems[45][46][47]. Thus, it can be assumed that the rough surface of the coatings formed in this work will facilitate attachment of osteoblasts and bone formation in vivo.…”
mentioning
confidence: 99%
“…AFM topography images for VDF-TeFE (a), HAP coating (c) and DCPA coating (e) and potential maps for VDF-TeFE (b), HAP coating (d) and DCPA coating (f).It is known that a rough surface structure of CaP coatings stimulates the attachment of osteoblasts and differentiation of multipotent MSC into osteoblasts in in vitro systems and bone formation in in vivo systems[45][46][47]. Thus, it can be assumed that the rough surface of the coatings formed in this work will facilitate attachment of osteoblasts and bone formation in vivo.…”
mentioning
confidence: 99%
“…Osseointegration is one of the types of integration, namely, the integration of an implant and bone tissue. In orthopaedic surgery, osseointegration was first mentioned when intramedullary implants with a bioactive coating (thin titanium rods) were used to treat fractures using combined techniques (with Ilizarov's frame; Petrovskaya et al, ; Popkov et al, ; Popkov et al, ). However, many orthopaedic surgeons believe that external fixation devices cause considerable discomfort for the patient, especially in prolonged osteosynthesis (Erinle, Rack, Linnik, & Saldun, ).…”
Section: Discussionmentioning
confidence: 99%
“…The combined techniques resulted in the reduction of the usual Ilizarov external fixation duration and good union rates [34][35][36]. Popkov et al [37] conducted a study which was aimed at revealing the differences in radiographic and histological outcomes of bone repair by using flexible intramedullary nailing combined with the Ilizarov external fixation versus the Ilizarov external fixation alone on a canine model of an open diaphyseal tibial fracture. They have concluded that their experimental study proves that the combination of the Ilizarov apparatus and flexible intramedullary nailing augments fixation stability of bone fragments, accelerates the repair of tibial shaft fractures, and can be used in clinical settings.…”
Section: Discussionmentioning
confidence: 99%